2001
DOI: 10.1097/00006534-200108000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Burn Scar of the Upper Extremities with Artificial Skin

Abstract: The management of upper-extremity burn contractures is a major challenge for plastic surgeons. After approval by the Food and Drug Administration, artificial skin (Integra) has been available in Taiwan since 1997. From January of 1997 to July of 1999, the authors applied artificial skin to 13 severely burned patients for the reconstruction of their upper extremities, resulting in an increased range of motion in the upper-extremity joints and improved skin quality. An additional benefit was the rapid reepitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(47 citation statements)
references
References 19 publications
0
42
0
5
Order By: Relevance
“…Integra (Johnson and Johnson, Hamburg, Germany) is a totally artificial material that is acellular and is composed of two skin-like layers. [3][4][5] The upper layer of the Silastic sheet is an epidermis-like structure, which controls water loss and prevents the invasion of microbes. The lower layer has a porous structure (pore size, 20 to 125 m), is composed of a cross-linked coprecipitate of bovine collagen and chondroitin-6-sulfate, and functions mainly as a template for dermal regeneration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Integra (Johnson and Johnson, Hamburg, Germany) is a totally artificial material that is acellular and is composed of two skin-like layers. [3][4][5] The upper layer of the Silastic sheet is an epidermis-like structure, which controls water loss and prevents the invasion of microbes. The lower layer has a porous structure (pore size, 20 to 125 m), is composed of a cross-linked coprecipitate of bovine collagen and chondroitin-6-sulfate, and functions mainly as a template for dermal regeneration.…”
mentioning
confidence: 99%
“…3 Several studies demonstrated good aesthetic and functional results in burn treatment and reconstruction; however, those studies also delineated the problems of the Integra take rate and the long interval between the surgical interventions. [3][4][5][6][7][8][9] In this study, we wanted to determine whether the Integra take rate could be improved with the use of fibrin glue (Tissucol, Baxter Deutschland GmbH, Heidelberg, Germany) and whether the interval of 21 days could be shortened with the use of negativepressure therapy (KCI, San Antonio, Texas).…”
mentioning
confidence: 99%
“…Entfernung der Silikonfolie ein ideales Bett für dünne Spalthaut, sodass mit deren Einheilung ein weitgehend intaktes Integument resultiert. Die positiven Erfahrungen mit Integra in der Akutversorgung von thermisch verletzten Patienten führten zu einer breiten Anwendung weltweit [2,5,8,10]. Für Anwendungen im Kindesalter konnten wir vergleichsweise früh Indikationen ausloten [9], die in einem verstärkten Einsatz bei Rekonstruktionen im Kindesalter mün-deten.…”
Section: Discussionunclassified
“…Sowohl in der Akutversorgung als auch in der rekonstruktiven Chirurgie werden kaum neuerliche Narbenhypertrophien beschrieben [2,5,9]. Hier kommt die exzellente Qualität der Neodermis mit der Möglichkeit einer erfolgreichen Transplantation dünner und (wo möglich) ungemeshter Spalthaut zum Tragen.…”
Section: Diskussionunclassified
“…Han et al berichteten anhand von 38 Patienten mit Basalzellkarzinomen im Gesichtsbereich im Journal of Craniofacial Surgery 2012 über die Anwendung von Spalthauttransplantaten [7]. Wesentliche Vorteile des dort verwendeten Verfahrens sehen die Autoren im transplantierten autologen Epidermisanteil, der den Wunddefekt sofort bedeckt und die schnelle Migration und Proliferation anhängender epidermaler Zellen sowie von Melanozyten ermöglicht [13][14][15][16]. Zusammenfassend lässt sich feststellen, dass die okuloplastische Chirurgie von einigen Besonderheiten u. a. dünnste Oberflächen-haut gekennzeichnet ist.…”
unclassified